The use of facebook on group collaboration among fast – track sophomores in felte, ulis, vnu: perception and implication = việc sử dụng facebook cho cộng tác nhóm của sinh viên năm 2 hệ chất lượng cao khoa sư phạm tiếng Anh: thực trạng và đề xuất - Trần, Minh Hằng (2020)
The 21st century has opened a new and state-of-the-art technology period to human beings. Among such modern products, Facebook, one of the social networks, has dramatically changed people’s lives and brought us closer than ever. However, people seem to normally consider Facebook as a tool for entertainment, not for any educational purpose. As there have been few studies on this aspect, this paper was conducted to explore the use of Facebook for group collaboration among fast-track sophomores at FELTE, ULIS, VNU. This study is basically aimed at giving a reference for students as well as course designers. Quantitative research was applied with a structured questionnaire and a semi-structure interview to investigate the use of Facebook for group collaboration. The participants, fast-track sophomores from Faculty of English Language Teaching Education (FELTE), University of Languages and International Studies (VNU), are studied in two main aspects namely group activities on Facebook; the pros and cons of using Facebook for group work. The result showed that fast-track sophomores often collaborated on Facebook such as discussing assignments, sharing opinions/ ideas with each other, etc. They found that it was convenient to use Facebook for group work as it was so popular and every member owned one, which made it become the common tool for group work. However, Facebook Messenger could be a big obstacle for members to follow the discussion. Besides, disobeyed members who were not on time for group discussion. Therefore, the solution has been come up with by ICT teachers such as note takers, punishment for late members or other applications usage, etc.